ҚАРАҚАЛПАҚ ДЕТЕКТИВ ПОВЕСТЛЕРИНДЕ КӨШПЕЛИ СЮЖЕТЛЕР - Алламуратова, З.М. (SCIENCE and SOCIETY, 2022)
The article analyzes and explores moving plots in detective novels from a scientific point of view. The article focuses on the stories of famous Karakalpak writers A.Bekimbetov, Sh.Seytov and U.Pirzhanov.